Steve Jobs : Thinking Differently - Lakin, Patricia (New York Aladdin, 2015)
A biography of Steve Jobs: visionary, entrepreneur, inventor, and cofounder of Apple.
Include Illustrations and Inddex
Keywords: United States -- Apple Computer, Inc -- Computer engineers